The Effect of Working Capital Management on Pharmaceutical Firm Profitability - Imron, Maulidatussa'adah; Aisjah, Siti (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
Purpose – This study aims to analyze the effect of working capital management on the profitability of pharmaceutical companies listed on the Indonesia Stock Exchange during the 2019–2023 period. Design/methodology/approach – This quantitative study uses secondary data from pharmaceutical companies listed on the Indonesia Stock Exchange. Working capital management is measured using the inventory conversion period, receivables collection period, payables deferral period, and cash conversion cycle, while profitability is measured using Return on Assets (ROA). The data were analyzed using multiple linear regression with SPSS version 29. Findings – The results indicate that the payables deferral period has a significant positive effect on profitability. Meanwhile, the inventory conversion period, receivables collection period, and cash conversion cycle do not have significant effects on profitability. These findings suggest that optimizing payment management can contribute to improved profitability in pharmaceutical companies. Originality/value – This study contributes to working capital management literature by examining the role of specific working capital components in determining profitability within Indonesia’s pharmaceutical industry. The findings provide practical insights for companies in managing short-term financial policies to enhance performance.